2018
DOI: 10.2478/jped-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Freedom and obedience in western education

Abstract: Education has to emphasize the characteristics which define Western democratic societies. In addition, it has to ensure the active and participative inclusion of each person in social life, where respect for human rights prevails over the person’s preferred ideology. Promoting these values in citizens not only guarantees the stability of the state, but also its constant progression and improvement. Beginning at the elementary level, the promotion of students’ critical spirit is recognized as a fundamental obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Children and adolescents, with their voice and involvement, show that they are subjects of rights, co-authors of their own learning processes. The school must take advantage of this potential to adapt to the change that its students demand, assuming an educational teleology that overcomes the contradiction of education, that is, that resolves the dichotomy between what education aspires to be, and what it really is [72]. In this study, children and adolescents have shown signs of maturity, having to overcome circumstances such as isolation, lack of socialization, and the deficit in much learning, which has generated stress and physical and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents, with their voice and involvement, show that they are subjects of rights, co-authors of their own learning processes. The school must take advantage of this potential to adapt to the change that its students demand, assuming an educational teleology that overcomes the contradiction of education, that is, that resolves the dichotomy between what education aspires to be, and what it really is [72]. In this study, children and adolescents have shown signs of maturity, having to overcome circumstances such as isolation, lack of socialization, and the deficit in much learning, which has generated stress and physical and mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Western education, and the dominantly Western-originated business school model, has been portrayed to promote obedience among students (Martin-Sanchez & Flores-Rodriguez, 2018), and to deter critical questioning of authority (Bridgman & Cummings, 2022). Naturally, if business schools remain geared toward “producing” the hired hands that keep capitalist businesses running smoothly (Khurana, 2010), there is no place for disobedience.…”
Section: Educating For Civil Disobedience: Disrupting Growthmentioning
confidence: 99%
“…Th erefore, the school must reproduce this model, in a sort of endogamic entity which transmits the formalized contents, the great meta-narratives and narratives approved and recognized as truths. In this setting, the teacher's authority is indisputable with an encyclopedic, vertical and passive teaching model (Martín-Sánchez & Flores-Rodríguez, 2018). It is a simplistic conception of Pedagogy and school, which assumes the methodology of Modernity.…”
Section: Traditional Pedagogymentioning
confidence: 99%
“…Th ere is no point in talking about new methodologies if the traditional chalkboard is replaced by a digital one, and the pedagogical method remains directive and authoritarian. What is is more, it is then that, before choosing a model, we must assume an educational teleology which overcomes the contradiction of education in the West, that is, that resolves the dichotomy between what education aims to be, and what is actually (Martín-Sánchez & Flores-Rodríguez, 2018). Precisely, in the case of Spain, the political alternation and confl ict in the educational fi eld has generated the creation and implementation of fi ve educational laws in the last 40 years that have only generated controversy and confl ict.…”
Section: Conclusion: Change and Uncertainty The Spanish School At The...mentioning
confidence: 99%